The universal health coverage challenge in Cameroon and strategies for sustainable reform - Ndung Ako Forbinake; Julius Mekolle Enongene; Bertrand Kealebong Asonglefac; Ajapnwa Akamin; Imelda Mbock; Clovis Tangem; Sangwe Clovis Nchinjoh; Aliyou Moustapha Chandini (Discover Public Health)
Abstract Over 179 million people worldwide are pushed into poverty each year due to out-of-pocket (OOP) health expenditures, with lower-income countries disproportionately affected. Cameroon’s ambition to achieve Universal Health Coverage (UHC) has garnered policy interest, yet significant systemic and financial barriers persist. This perspective critically examines the financial and structural limitations confronting Cameroon’s UHC journey. As of 2022, government health expenditure represented only 3.9% of the Gross Domestic Product (GDP), with per capita spending at approximately US$58. The health system remains heavily dependent on private household contributions, with Domestic Private Health Expenditure accounting for 71.8% of total health financing. The projected cost of implementing a basic UHC package is estimated at US$2.8 billion over five years, equivalent to 29% of the 2021 national budget—highlighting a significant funding gap. Cameroon’s rising public debt, which reached US$24 billion (45.6% of GDP) by the end of 2024, further constrains fiscal space. Additionally, legal and institutional frameworks are underdeveloped: no UHC-specific legislation exists, and outdated fee schedules remain in use despite changing economic conditions. Compounding these issues, the predominance of informal employment, representing 90% of the workforce, poses challenges to broad-based insurance enrollment and revenue generation. To advance UHC, Cameroon must prioritise legal reform, expand fiscal space through innovative and equitable taxation, and strengthen public financial management. Addressing foundational health system weaknesses is critical. Although the challenges are substantial, a strategic, equity-driven approach grounded in political-will could enable Cameroon to progress meaningfully toward achieving UHC.